Development of Self-Sanitizing Door Handle Automation - Chan, Yu Xuan; Loh, Ee Herng; Ma'radzi, Ahmad Alabqari; Lim, Kian Ann (Multidisciplinary Applied Research and Innovation, 2023)
Lately, sanitising hands is required for people before entering a building but due to manual hand sanitiser, not all the customers will sanitise their hands before entering a building. Thus, the development of a system self-sanitising door handle allows people to open the door while keeping their hands and the surface of the door handle clean where the self-sanitising door handle can operate manually or automatically. This thesis covers the details of the theory and working principles of the self-sanitising door handle. This thesis explains and discusses the methods of developing a self-sanitising door handle using Tinkercad Simulation and Arduino Uno. Furthermore, the operation of the self-sanitising door handle is presented in this thesis. The experimental data and simulation results are all provided and discussed. Both self-sanitising door handle prototype experimental results and simulation in Tinkercad results have been recorded and compared. In conclusion, the theoretical results are supported by the experimental and simulation results.